Nodal staging convergence for HPV− and HPV+ oropharyngeal carcinoma. Issue 10 (17th February 2021) - Ho, Allen S.; Luu, Michael; Kim, Sungjin; Tighiouart, Mourad; Mita, Alain C.; Scher, Kevin S.; Mallen‐St. Clair, Jon; Walgama, Evan S.; Lin, De‐Chen; Nguyen, Anthony T.; Zumsteg, Zachary S.
Abstract : Background: Modern disease staging systems have restructured human papillomavirus (HPV)‐negative (HPV−) and HPV‐positive (HPV+) oropharyngeal carcinoma (OPC) into distinct pathologic nodal systems. Given that quantitative lymph node (LN) burden is the dominant prognostic factor in most head and neck cancers, we investigated whether HPV− and HPV+ OPC warrant divergent pathologic nodal classification. Methods: Multivariable Cox regression models of OPC surgical patients identified via U.S. cancer registry data were constructed to determine associations between survival and nodal characteristics. Nonlinear associations between metastatic LN number and survival were modeled with restricted cubic splines. Recursive partitioning analysis (RPA) was used to derive unbiased nodal schema. Results: Mortality risk escalated continuously with each successive positive LN in both OPC subtypes, with analogous slope. Survival hazard increased by 18.5% (hazard ratio [HR], 1.19 [95% CI, 1.16‐1.21]; P < .001) and 19.1% (HR, 1.19 [95% CI, 1.17‐1.21]; P < .001), with each added positive LN for HPV− and HPV+ OPC, respectively, up to identical change points of 5 positive LNs. Extranodal extension (ENE) was an independent predictor of HPV− OPC (HR, 1.55 [95% CI, 1.20‐1.99]; P < .001) and HPV+ OPC (HR 1.73 [95% CI, 1.36‐2.20]; P < .001) mortality. In RPA for both diseases, metastatic LN was the principal nodal covariate driving survival, with ENE as a secondary determinant. Given the similarities across analyses, we propose a concise, unifying HPV−/HPV+ OPC pathologic nodal classification schema: N1, 1‐5 LN+/ENE−; N2, 1‐5 LN+/ENE+; N3, >5 LN+. Conclusion: HPV− and HPV+ OPC exhibit parallel relationships between nodal characteristics and relative mortality. In both diseases, metastatic LN number represents the principal nodal covariate governing survival, with ENE being an influential secondary element. A consolidated OPC pathologic nodal staging system that is based on these covariates may best convey prognosis. Lay Summary: The current nodal staging system for oropharyngeal carcinoma (OPC) has divided human papillomavirus (HPV)‐negative (HPV−) and HPV‐positive (HPV+) OPC into distinct systems that rely upon criteria that establish them as separate entities, a complexity that may undermine the core objective of staging schema to clearly communicate prognosis. Our large‐scale analysis revealed that HPV− and HPV+ pathologic nodal staging systems in fact mirror each other. Multiple analyses produced conspicuously similar nodal staging systems, with metastatic lymph node number and extranodal extension delineating the highest risk groups that shape prognosis. We propose unifying HPV− and HPV+ nodal systems to best streamline prognostication and maximize staging accuracy. Abstract : Human papillomavirus (HPV)‐negative ( HPV−) and HPV‐positive (HPV+) oropharyngeal carcinoma (OPC) exhibit parallel nodal relationships, with metastatic lymph node burden and extranodal extension representing the principal nodal covariates governing survival. A concise, unified HPV−/HPV+ OPC pathologic nodal staging system that is based on these elements may best convey prognosis.